THU0289 B-cell activating factor gene expression in urinary sample and renal biopsy for monitoring disease activity in lupus nephritis. (15th June 2017) - Retamozo, S; Mas, L; Salinas, MJ Haye; Saurit, V; Caeiro, F; Diller, A; Fuente, J De La; Angelina, M; Benzaquen, NR; Pirola, JP; Alvarellos, A; Alvarellos, T
Abstract : Objectives: To evaluate BLyS as biomarker in disease activity in urinary sample and renal biopsy from patients with LN. Methods: Retrospective study. Between June 2009 and October 2013, 32 patients with SLE and LN fullfilling SLE classification criteria of ACR 1997 were included. The renal biopsies were evaluated according to the ISN/RPS classification system. The gene expression levels of BLyS were quantified using Quantitative Real Time PCR (QPCR). The relative quantification method was used for analysis, where Ct was normalized to an endogenous control β2Microglobulina (β2M) (ΔCt BLyS). The data expressed as ΔCt are inversely proportional to gene expression level. The value of BLyS is expressed as median (M) and interquartile range (IQR) for filing a non-normal distribution. Results: 26 (81.3%) patients were female with a mean age at diagnosis of 26.9±13 years and 31.9±29 years at the time of renal biopsy. The SLEDAI at the time of biopsy was 10.5 (IQR 0–15.7) and SLICC ≥1 in 13 (32.5%), hypocomplementemia 13/31 (41.9%) and positive DNA in 11/29 (37.9%) patients. Biopsies from patients with proteinuria ≥0.5 and renal failure (RF) (n=23, 71.9%), proteinuria isolated (n=14, 43.8%), LN remission. The value of the BLyS gene expression in renal biopsy was 8.09 (IQR 7.37–9.16) and BLyS in urinary sample was 6.45 (IQR 5.62–7.76). Conclusions: BLyS detection in urinary samples could be a potential biomarker for predicting lupus nephritis activity. Our data confirm that the BLyS as urinary biomarker is present in patients with active renal disease especially in patients with proliferative glomerulonephritis. Disclosure of Interest: None declared